Kreativitas Netizen dalam Strategi Pemasaran Restoran untuk Menarik Wisatawan (Studi Kasus Restoran Hotel Best Western Premier La Grande Bandung) - Sukarana, Murdiani; Anas, Muhammad (Jurnal Master Pariwisata (JUMPA); Volume 08, Nomor 01, Juli 2021DO - 10.24843/JUMPA.2021.v08.i01.p12, 2021)
The aim of this research is to explain the role of hotels in promoting their restaurants and create new ideas on the resources owned by hotels to develop marketing techniques with digital and contemporary channels. The research was conducted at the Restaurant Best Western Premiere La Grande Bandung. This research is a qualitative research with data and analysis results presented in the form of descriptions through observation methods, in-dept interviews, and documentation. Data analysis technique with steps; data processing, data analysis, and interpretation of data analysis results. The result of this research is that marketing media through the internet (digital promotion) has a very significant effect on visitors to the Best Western Premiere La Grande Hotel Restaurant, Bandung. Among the online media used by restaurant management, Instagram has the greatest impact on promotional results to visitors. Consecutively the role of digital media in marketing results, namely 45% of the Instagram hashtag, 32% of the website and 23% of the e-brochure. Thus the digital marketing strategy has a high level of effectiveness in introducing hotels in general and specifically at the Restaurant Hotel Best Western La Grande Bandung. Keywords: marketing strategy, creativity, netizen